1993
DOI: 10.1073/pnas.90.15.7089
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum virus resistance in transgenic plants expressing pokeweed antiviral protein.

Abstract: Exogenous application of pokeweed antiviral protein (PAP), a ribosome-inhibiting protein found in the cell walls of Phytolacca americana (pokeweed), protects heterologous plants from viral infection. A cDNA clone for PAP was isolated and introduced into tobacco and potato plants by transformation with Agrobacterium tumefaciens. Transgenic plants that expressed either PAP or a double mutant derivative of PAP showed resistance to infection by different viruses. Resistance was effective against both mechanical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
165
2
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(176 citation statements)
references
References 23 publications
3
165
2
6
Order By: Relevance
“…PAP also inhibits growth of tumor cells (Stirpe et al, 1992). Positive correlations were reported between RIP-catalyzed depurination of tobacco ribosomes and antiviral activity of exogenously applied RIPs (Taylor et al, 1994) and between the extent of inhibition of virus infection by PAP and the depurination of host ribosomes (Chen et al, 1992).We reported that transgenic tobacco and potato plants expressing PAP show broad-spectrum resistance to infection by different viruses (Lodge et al, 1993). In this paper we studied the mechanism of this resistance by grafting wild-type tobacco plants on transgenic tobacco plants expressing PAP.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…PAP also inhibits growth of tumor cells (Stirpe et al, 1992). Positive correlations were reported between RIP-catalyzed depurination of tobacco ribosomes and antiviral activity of exogenously applied RIPs (Taylor et al, 1994) and between the extent of inhibition of virus infection by PAP and the depurination of host ribosomes (Chen et al, 1992).We reported that transgenic tobacco and potato plants expressing PAP show broad-spectrum resistance to infection by different viruses (Lodge et al, 1993). In this paper we studied the mechanism of this resistance by grafting wild-type tobacco plants on transgenic tobacco plants expressing PAP.…”
supporting
confidence: 52%
“…We reported that transgenic tobacco and potato plants expressing PAP show broad-spectrum resistance to infection by different viruses (Lodge et al, 1993). In this paper we studied the mechanism of this resistance by grafting wild-type tobacco plants on transgenic tobacco plants expressing PAP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that RIPs may have a defensive role against viruses is supported by the resistance acquired by plants transfected with RIP genes [19][20][21] and, indirectly, by the expression of a RIP in tissues of sugar beet plants consequent to…”
Section: A Characteristic Of Rips Is Their Inhibitory Effect On Proteinmentioning
confidence: 99%
“…However, despite results indicating that the exogenous application of RIPs to plants and the expression of transgenes confers both viral and fungal resistance (Logemann et al, 1992 ;Lodge et al, 1993), there is no compelling evidence that this is the physiological role of these proteins in vivo.…”
Section: mentioning
confidence: 99%